Decentering Power in Research with Criminalized Women: A Case for Photo-Elicitation Interviewing. Issue 1 (2nd January 2017) - Rumpf, Cesraéa
ABSTRACT: This article contributes to the project of developing a visual criminology that reclaims social relationships and the humanity and visibility of criminalized people and strives to disrupt the ideological and political underpinnings of mass incarceration and the state's reliance on punitive responses to social inequality. Using photo-elicitation interviewing (PEI), I draw on qualitative research with 36 formerly incarcerated women living in Chicago. I review PEI's potential to disrupt the power differential between researchers and participants and to include research participants as collaborators in knowledge production. I examine how limitations imposed by an Institutional Review Board created ethical concerns about representing women's images and constrained women's role in the coproduction of knowledge. I argue that PEI based on participant-generated images can help to overcome some of the ethical and methodological tensions encountered in visual criminology.